Dredger Design for River Dredging in Sampang - Muhammad Musta'in; Moh Fadil; Taufan Prasetyo; Heni Siswanti (POLITEKNIK NEGERI BENGKALIS, 2020)
At The Kemuning Sampang River is silting up. The solution of the silting up is by dredging the Kemuning river. Dredging in the Kemuning river has been carried out, but using heavy equipment in the form of excavators. The excavator needs a float in the form of a relatively large pontoon, so it takes a long time and the work becomes obstructed, and the dredging range is very limited.This research method is to identify the field or formulation of the problem and then look for references that will be the basis and guide in making this research. Furthermore, collecting river data, determine the main size of the ship and the dredger design process.The results of this study are in the form of dredger design planning which has more free movement and further dredging range. The design of dredges includes lines plans composed of three projected ship images, namely body plan, half breadth plan and sheer plan. Then the general arrangement consists of the layout of the room layout and the placement of the dredger.